Mathematical thoughts within the Sámi culture - Jannok-Nutti, Ylva (Luleå tekniska universitet, Pedagogik, språk och Ämnesdidaktik, 2008)
The paper is an attempt to discuss a multi-cultural view of mathematics or mathematical thoughts in connection to the education in mathematics in the Sámi Schools. The discussion takes its start from a research-project where the aim was to describe and analyze mathematical thought within the Sámi culture. The research already indicates that there are diff erent conceptions within the Sámi culture, which could be used in the education in mathematics in the Sami schools. Godkänd; 2006; 20071213 (cefa)